An exploration on COVID-19 vaccination motivation patterns from the perspective of the Chaxu culture in metropolis of China: A multi-center study - Huang, Jiaoling; Jiang, Zhiyun; Gu, Jie; Yang, Yuqi; Yan, Yuge; Gu, Xiaoqing; Bai, Yundan; Liang, Yan (Frontiers in Public Health, 2022)
Objectives: Chaxugeju is a very special Chinese culture following a self-centered and outward expanding social network, which might be a significant culture factor for vaccination behavior. This study aimed to identify the motivation pattern in China, and paid special focus on socio-economic status (SES), region, and migration. Methods: We used a latent class analysis, with a sample of 12,432 participants collected in China from April to June, to identify the COVID-19 vaccination motivation patterns. Multinomial logistic regression models were utilized to separately explore associations between SES, migration, region, and COVID-19 vaccination motivation patterns. Results: Three COVID-19 vaccination motivation patterns were identified: Self-protection (41.9%), Trust & Self-protection (38.5%), and Trust and Differential Protection (19.6%). Participants with higher income were more likely to be Trust & Self-protection, and when income is more than 50000 CNY per month, they are more likely to be self-protection. Professional/white collar were more likely to be Self-protection. Participants from Shenzhen were more likely to be Trust & Differential protection. The moderating effects of gender were found for income and region. Gender does not moderate the associations of occupation or migration and COVID-19 vaccination motivation patterns. Conclusions: Three motivational patterns were identified in which the Trust & Differential Pattern followed the traditional self-family-community Chaxu circle. However, the Chaxu motivation pattern was not the dominant one which might be weakened by SES. Migration and Shenzhen preserved the traditional social network, keeping in the trust and differential pattern. All of these factors in various cultural contexts should be considered when promoting vaccines.